Habitat associations of bats in Northern Ireland: implications for conservation ... - Russ, J.M; Montgomery, W.I (Zenodo, 2002)
(Uploaded by Plazi for the Bat Literature Project) Agricultural intensification in Northern Ireland has brought about large-scale changes to the landscape with a detrimental effect on biodiversity. Between 1996 and 1998, we surveyed a stratified random sample of 1 km squares for bats using a spot-sample technique and time expansion bat detector to establish linear and area habitat associations. Bats strongly selected water bodies with bankside vegetation, treelines, and deciduous and mixed woodland edge, avoiding open areas such as upland/unimproved grassland and improved grassland. Of three sympatric pipistrelle species (Pipistrellus pipistrellus, P. pygmaeus and P. nathusii), two were shown to forage in different habitats; P. pipistrellus being more of a 'generalist', foraging in a wider variety of habitats than P. pygmaeus, a 'specialist' which foraged in a smaller range of habitats. Nyctalus leisleri selected parkland/amenity grassland, deciduous woodland edge and rivers/canals and avoided improved ...